2010
DOI: 10.1097/ana.0b013e3181df0600
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Postoperative Pain After Craniotomy

Abstract: logistic regression and chi using SPSS program (Windows, version 12.0). During the first 24 hours 87% of the patients experienced pain (NRS 1 to 3: 32%, NRS 4 to 7: 44%, NRS 8 to 10: 11%). For postoperative analgesia, the opioid piritramide (a mu-receptor agonist) was administered to 70% and nonopiod analgesics to 73% of the patients. The probability of experiencing postcraniotomy pain was reduced by 3% for each year of life. Maintenance of anesthesia with sevoflurane increased the probability of suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 31 publications
10
75
3
3
Order By: Relevance
“…In the largest case series, two-thirds of the patients reported moderate-to-severe headache after craniotomy [4]. A more recent study indicated that 55% of craniotomy patients report moderate-to-severe pain in the first 24 hours [13]. Our results are consistent with previous reports, with 52% of the diclofenac patients and 73% of the control patients reporting moderate-to-severe pain the day after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…In the largest case series, two-thirds of the patients reported moderate-to-severe headache after craniotomy [4]. A more recent study indicated that 55% of craniotomy patients report moderate-to-severe pain in the first 24 hours [13]. Our results are consistent with previous reports, with 52% of the diclofenac patients and 73% of the control patients reporting moderate-to-severe pain the day after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Prospective observational studies showed that a substantial number of patients (approximately 50%) suffered from moderate to severe pain during the first postoperative day after craniotomy 3436. In a recent study by Mordhorst et al,34 55% of patients had moderate or severe postoperative pain in the first 24 hours following craniotomy. This study had a result similar to the pilot study by De Benedittis et al,37 in which 60% of patients experienced postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Mordhorst et al . [2], 55% of patients had moderate or severe postoperative pain in the first 24 hours following craniotomy. This study had a similar result to the pilot study by De Benedittis et al .…”
Section: Introductionmentioning
confidence: 99%